Administration of Oral Sorghum Seed Extract (Sorghum bicolor L.) Increased Pancreatic Beta Cells Count but did not Reduce Glycated Albumin Levels in Male Wistar Rats (Rattus Norvegicus) with Diabetes Mellitus - Efrida Sumawati; Wimpie Pangkahila; A.A. Gede Budhiarta (IJAAM (Indonesian Journal of Anti-Aging Medicine), 2020)
Background: It is required a long time of diabetes mellitus treatment, such as doing general activities or even insulin. Sorghum is a plant that contains antioxidants. The aim of this research was to prove the oral administration of Sorghum Seed Extract (Sorghum bicolor L.) in increasing the pancreatic beta cells count but did not reduce the levels of glycated albumin in male Wistar rats (Rattus norvegicus) with Diabetes Mellitus. Method: This study used experimental post-test only group design. 36 male Wistar rats were used and injected with the nicotinamide and streptozotocin intraperitoneally. Rats were divided into 2 groups, the control group (n=18) was administrated with distilled water at a dose of 2cc/200g body weight of rats. The the treatment group (n=18) was administrated with ethanol extract of sorghum seeds with a dose of 80 mg/kgBW of rats/ day. The post-test of glycated albumin levels and histopathology examination of pancreatic beta cells count were performed. Results: The mean of pancreatic β cells count in the control group was 64.31 ± 19.397. It was lower than the treatment group which was 119.44 ± 33.799 (p <0.005). The mean results glycated albumin level of the research in the control group was 8.577 ± 3.105 ng/ml and in the treatment group was 9,191 ± 3,014 ng/ml (p> 0,05), therefore it was not proven. Conclusion: The administration of ethanol extract of sorghum seeds increased pancreatic β cells count, but it did not reduce glycated albumin levels in male Wistar rats (Rattus Norvegicus) with Diabetes Mellitus.